Ultrasound evaluation of arterial anastomosis of the forehead. (26th August 2018) - Tansatit, Tanvaa; Phumyoo, Thirawass; Jitaree, Benrita; Sawatwong, Worapat; Rungsawang, Chalermquan; Jiirasutat, Nuttapatch; Sahraoui, Yasmina M. E.; Lee, Joo Heon
Summary: Background: Color Doppler ultrasound has a potential role as an imaging guide in aiding filler injections which are blinded procedures. Objective: This study investigated the forehead arteries and provided insight into their anastomoses. This was performed by challenging their function to provide blood through these anastomoses when the main artery was temporary occluded by compression. Methods: Three arteries were identified on each side of the forehead, the supratrochlear, the supraorbital and the superficial temporal arteries. Under ultrasound monitoring, each target artery and corresponding anastomosis was studied separately by compressions performed in a sequential and accumulative manner. Results: Data from the current study imply that accidental cannulation of either the supratrochlear artery or the supraorbital artery can cause ophthalmic artery embolization in every case recorded. If the frontal branch of the superficial temporal artery is cannulated, the chance of blindness as a complication occurs in one fifth of volunteers. Anastomosis between both sides of the terminal branches of ophthalmic arteries creates the possibility of bilateral ocular complications when accidental cannulation occurs at one of these branches, especially the supratrochlear artery. Thus, injury to the supratrochlear artery carries a greater risk of complication than the supraorbital artery. Conclusion: These findings emphasize that the chance of ocular complication is less when accidental cannulation occurs at the superficial temporal artery compared with injury to the supratrochlear or the supraorbital arteries as the terminal branches of the ophthalmic artery. Ultrasound can assist in the identification and evaluation of all the arteries at risk, thus avoiding the occurrence of vascular complications.